Evaluating the accuracy (precision and trueness) of conventional and digital Intraoral Impression Technique. - Lana Shwan Jalal; Dara Hamarashid Saeed (Erbil Dental Journal)
Background and Objectives: This study aims to compare and evaluate the accuracy of the conventional and digital intraoral scanner impression approaches of the maxillary edentulous arch with indirect fixed restorations.